Indonesia’s Emerging Role as a Key Donor in South-South Cooperation - Azis, Aswin Ariyanto (Global and Policy Journal of International Relations, 2025)
Considering Indonesia’s transformation into a new donor within the framework of South-South Cooperation (SSC), this study explores the strategic and geopolitical significance of its engagement in SSC. The problem lies in understanding how Indonesia’s role aligns with its national interests while addressing global development challenges. The aim is to identify the strategies and implications of Indonesia’s foreign aid policy in SSC, focusing on its justification as a Middle Income Country and a developing economy. To this end, the author proceeds by using a qualitative approach, analyzing secondary data from policy documents, international reports, and historical records related to Indonesia’s engagement in SSC. In this way, it can be observed that Indonesia’s shift from a recipient to a new donor reflects its commitment to reducing dependency among the Global South countries while strengthening its image and influence at the international level. This allows the author to conclude that Indonesia’s proactive role in SSC not only strengthens its diplomatic and economic position but also underlines its long-term strategy to support sustainable development and foster South-South solidarity.